The potential contribution of Li Jinhui’s compositions and preschool music textbooks to preschool music education in contemporary China - Loo, Fung Chiat; Huang, Yi (International Academy of Technology, Education and Development, 2024)
Understanding the contributions of past composers enriches music education and promotes its development. Li Jinhui (1891–1967) was an eminent Chinese composer whose works included popular music and children’s song and dance drama (歌舞剧). He was considered the pioneer of this genre in China and contributed to various fields, such as music, dance, literature, drama, and education. Most research has focused on Li’s popular music and literary works while his valuable contributions to the field of children’s music education have been consistently overlooked. This study attempts to fill this research gap by tracing the development of children’s music compositions and preschool music textbooks derived from Jinhui’s work, with the aim of determining his potential contributions to contemporary Chinese preschool music education. It analyzed kindergarten music textbooks that developed from Li’s textbooks to clarify the potential value of his music textbooks. Findings revealed the considerable influence of Jinhui’s work on contemporary children's music in China. The study findings contribute to the reassessment of the potential value of his works and teaching materials